The Impact of Project Based Learning Using Podcast on Student Speaking Skill - Pratiwi, Selvy Amylia Ayu; Rukminingsih , Rukminingsih; Dwi Mumtazah , Livia (Scripta : English Department Journal, 2024)
This research aims to find out whether students who were given the PjBL method using podcasts achieved better speaking skills compared to students who were given the conventional method. The population in this study was 70 students devided into experimental class and control class from one of the senior high schools in Jombang, East Java. The sample was taken by using proposive sample which consisted of 2 science classes with 35 students for each class. The researcher used purposive sampling to select 2 classes from the population that would be used as the experimental class and the control class. This research uses a quantitative experimental design method. Based on the result of inferential statistic, it can be seen that sig. (2 tailed) value 0.00 <0.05, so it can be seen that was significant different effect. In the experimental class the teacher provides a project-based learning method in students' learning of speaking skills, students are more interested and more effective in the learning process. It can be seen that the PjBL method is very good for use in the teaching and learning process. researchers suggest using other skills in teaching.